2022
DOI: 10.1096/fj.202101862r
|View full text |Cite
|
Sign up to set email alerts
|

Exploiting the tumor immune microenvironment and immunometabolism using mitochondria‐targeted drugs: Challenges and opportunities in racial disparity and cancer outcome research

Abstract: Black and Hispanic cancer patients have a higher incidence of cancer mortality. Many factors (e.g., socioeconomic differences, insufficient access to healthcare) contribute to racial disparity. Emerging research implicates biological disparity in cancer outcomes. Studies show distinct differences in the tumor immune microenvironment (TIME) in Black cancer patients. Studies also have linked altered mitochondrial metabolism to changes in immune cell activation in TIME. Recent publications revealed a novel immuno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 99 publications
(250 reference statements)
0
7
0
Order By: Relevance
“…Studies have shown that ATO can also inhibit cancer cell viability by targeting the mitochondrial complex III [ 19 , 22 ], which increases the ROS levels within cancer cells. In addition, it has been reported that ATO can increase oxidative stress in vitro [ 24 ] and reduce hypoxia in vivo [ 19 ], which may enhance T cell-based cancer immunotherapy by alleviating the hypoxic conditions within the tumor microenvironment [ 50 ]. As we know, ferroptosis is a ROS-dependent form of cell death, ROS-inducing drugs (such as doxorubicin, gemcitabine, paclitaxel, 5-fluorouracil, bortezomib, and arsenic trioxide) in combination with Cyst(e)inase is considered to be new therapeutic opportunities for ferroptosis-based anticancer therapy [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that ATO can also inhibit cancer cell viability by targeting the mitochondrial complex III [ 19 , 22 ], which increases the ROS levels within cancer cells. In addition, it has been reported that ATO can increase oxidative stress in vitro [ 24 ] and reduce hypoxia in vivo [ 19 ], which may enhance T cell-based cancer immunotherapy by alleviating the hypoxic conditions within the tumor microenvironment [ 50 ]. As we know, ferroptosis is a ROS-dependent form of cell death, ROS-inducing drugs (such as doxorubicin, gemcitabine, paclitaxel, 5-fluorouracil, bortezomib, and arsenic trioxide) in combination with Cyst(e)inase is considered to be new therapeutic opportunities for ferroptosis-based anticancer therapy [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nazha and colleagues (39) addressed the underrepresentation of minority ethnic groups in clinical trials and showed that AAs represent less than 4% of all patients enrolled. Kalyanaraman and colleagues (40) proposed that altered mitochondrial oxidative metabolism and differences in the tumor immune microenvironment are critical determinants of poor clinical outcomes among AA patients. Finally, Kakarla and colleagues (41) summarized the impact of racial disparities for different cancer types (prostate, breast, ovarian and uterine, digestive, urinary, and respiratory) and concluded that aggressive forms of disease and overall mortality are higher in AAs compared with other races.…”
Section: Discussionmentioning
confidence: 99%
“…Recent publications suggest that race and ethnicity are factors that affect mitochondrial metabolism in cancer cells, and that mitochondrial metabolism in white cancer patients is considerably different than in patients from other racial and ethnic groups [67][68][69][70]. Studies have revealed distinct differences in the TME in Black cancer patients.…”
Section: Mitochondria Metabolism and Racial Disparity In Cancermentioning
confidence: 99%